Answer:
ABD = CDB
AB is parallel to DC
Step-by-step explanation:
angle a and c are right angles so they are equal and angle b and d are equal because they have a line that touch both letters
AB and DC are parellel because they are the same looking lines just on oppisite sides
Answer: p=7/2=3.5
Step-by-step explanation:
Given
-4p+9=-5
Subtract 9 on both sides
-4p+9-9=-5-9
-4p=-14
Divide -4 on both sides
-4p/-4=-14/-4
p=7/2=3.5
Hope this helps!! :)
Please let me know if you have any questions
Answer:The better buy Option is A
Step-by-step explanation:
Question:
![\frac{2tan30^{\circ}}{1 + tan^2(30^{\circ})}](https://tex.z-dn.net/?f=%5Cfrac%7B2tan30%5E%7B%5Ccirc%7D%7D%7B1%20%2B%20tan%5E2%2830%5E%7B%5Ccirc%7D%29%7D)
Answer:
![\frac{2tan30^{\circ}}{1 + tan^2(30^{\circ})}](https://tex.z-dn.net/?f=%5Cfrac%7B2tan30%5E%7B%5Ccirc%7D%7D%7B1%20%2B%20tan%5E2%2830%5E%7B%5Ccirc%7D%29%7D)
![= sin(60^{\circ})](https://tex.z-dn.net/?f=%3D%20sin%2860%5E%7B%5Ccirc%7D%29)
Step-by-step explanation:
Given
![\frac{2tan30^{\circ}}{1 + tan^2(30^{\circ})}](https://tex.z-dn.net/?f=%5Cfrac%7B2tan30%5E%7B%5Ccirc%7D%7D%7B1%20%2B%20tan%5E2%2830%5E%7B%5Ccirc%7D%29%7D)
Required
Simplify
In trigonometry:
![tan(30^{\circ}) = \frac{1}{\sqrt{3}}](https://tex.z-dn.net/?f=tan%2830%5E%7B%5Ccirc%7D%29%20%3D%20%5Cfrac%7B1%7D%7B%5Csqrt%7B3%7D%7D)
So, the expression becomes:
![= \frac{2 * \frac{1}{\sqrt{3}}}{1 + (\frac{1}{\sqrt{3}})^2}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B2%20%2A%20%5Cfrac%7B1%7D%7B%5Csqrt%7B3%7D%7D%7D%7B1%20%2B%20%28%5Cfrac%7B1%7D%7B%5Csqrt%7B3%7D%7D%29%5E2%7D)
Simplify the denominator
![= \frac{2 * \frac{1}{\sqrt{3}}}{1 + \frac{1}{3}}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B2%20%2A%20%5Cfrac%7B1%7D%7B%5Csqrt%7B3%7D%7D%7D%7B1%20%2B%20%5Cfrac%7B1%7D%7B3%7D%7D)
![= \frac{\frac{2}{\sqrt{3}}}{1 + \frac{1}{3}}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B%5Cfrac%7B2%7D%7B%5Csqrt%7B3%7D%7D%7D%7B1%20%2B%20%5Cfrac%7B1%7D%7B3%7D%7D)
![= \frac{\frac{2}{\sqrt{3}}}{ \frac{3+1}{3}}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B%5Cfrac%7B2%7D%7B%5Csqrt%7B3%7D%7D%7D%7B%20%5Cfrac%7B3%2B1%7D%7B3%7D%7D)
![= \frac{\frac{2}{\sqrt{3}}}{ \frac{4}{3}}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B%5Cfrac%7B2%7D%7B%5Csqrt%7B3%7D%7D%7D%7B%20%5Cfrac%7B4%7D%7B3%7D%7D)
Express the fraction as:
![\frac{2tan30^{\circ}}{1 + tan^2(30^{\circ})}](https://tex.z-dn.net/?f=%5Cfrac%7B2tan30%5E%7B%5Ccirc%7D%7D%7B1%20%2B%20tan%5E2%2830%5E%7B%5Ccirc%7D%29%7D)
![= \frac{2}{\sqrt 3} / \frac{4}{3}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B2%7D%7B%5Csqrt%203%7D%20%2F%20%5Cfrac%7B4%7D%7B3%7D)
![= \frac{2}{\sqrt 3} * \frac{3}{4}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B2%7D%7B%5Csqrt%203%7D%20%2A%20%5Cfrac%7B3%7D%7B4%7D)
![= \frac{1}{\sqrt 3} * \frac{3}{2}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B1%7D%7B%5Csqrt%203%7D%20%2A%20%5Cfrac%7B3%7D%7B2%7D)
![= \frac{3}{2\sqrt 3}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B3%7D%7B2%5Csqrt%203%7D)
Rationalize
![= \frac{3}{2\sqrt 3} * \frac{\sqrt{3}}{\sqrt{3}}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B3%7D%7B2%5Csqrt%203%7D%20%2A%20%5Cfrac%7B%5Csqrt%7B3%7D%7D%7B%5Csqrt%7B3%7D%7D)
![= \frac{3\sqrt{3}}{2* 3}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B3%5Csqrt%7B3%7D%7D%7B2%2A%203%7D)
![= \frac{\sqrt{3}}{2}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B%5Csqrt%7B3%7D%7D%7B2%7D)
In trigonometry:
![sin(60^{\circ}) = \frac{\sqrt{3}}{2}](https://tex.z-dn.net/?f=sin%2860%5E%7B%5Ccirc%7D%29%20%3D%20%20%5Cfrac%7B%5Csqrt%7B3%7D%7D%7B2%7D)
Hence:
![\frac{2tan30^{\circ}}{1 + tan^2(30^{\circ})}](https://tex.z-dn.net/?f=%5Cfrac%7B2tan30%5E%7B%5Ccirc%7D%7D%7B1%20%2B%20tan%5E2%2830%5E%7B%5Ccirc%7D%29%7D)
![= sin(60^{\circ})](https://tex.z-dn.net/?f=%3D%20sin%2860%5E%7B%5Ccirc%7D%29)
Answer:
![\frac{xe^{7x}}{7} + \frac{e^{7x}}{49}](https://tex.z-dn.net/?f=%5Cfrac%7Bxe%5E%7B7x%7D%7D%7B7%7D%20%2B%20%5Cfrac%7Be%5E%7B7x%7D%7D%7B49%7D)
Step-by-step explanation:
Given the integral equation
![\int\limits{xe^{7x}} \, dx \\](https://tex.z-dn.net/?f=%5Cint%5Climits%7Bxe%5E%7B7x%7D%7D%20%5C%2C%20dx%20%5C%5C)
According to integration by part;
![\int\limits {u} \, dv = uv + \int\limits {v} \, du](https://tex.z-dn.net/?f=%5Cint%5Climits%20%7Bu%7D%20%5C%2C%20dv%20%3D%20uv%20%2B%20%20%5Cint%5Climits%20%7Bv%7D%20%5C%2C%20du)
u = x, dv = e^7x
du/dx = 1
du = dx
![v = \int\limits {e^{7x}} \, dx \\v = e^7x/7](https://tex.z-dn.net/?f=v%20%3D%20%5Cint%5Climits%20%7Be%5E%7B7x%7D%7D%20%5C%2C%20dx%20%5C%5Cv%20%3D%20e%5E7x%2F7)
Substitute the given values into the formula;
![\int\limits {xe^{7x}} \, dx = x(e^{7x}/7) + \int\limits ({e^{7x}/7}) \, dx\\\int\limits {xe^{7x}} \, dx = \frac{xe^{7x}}{7} + \frac{e^{7x}}{7*7} \\\int\limits {xe^{7x}} \, dx = \frac{xe^{7x}}{7} + \frac{e^{7x}}{49}](https://tex.z-dn.net/?f=%5Cint%5Climits%20%7Bxe%5E%7B7x%7D%7D%20%5C%2C%20dx%20%3D%20x%28e%5E%7B7x%7D%2F7%29%20%2B%20%5Cint%5Climits%20%28%7Be%5E%7B7x%7D%2F7%7D%29%20%5C%2C%20dx%5C%5C%5Cint%5Climits%20%7Bxe%5E%7B7x%7D%7D%20%5C%2C%20dx%20%3D%20%5Cfrac%7Bxe%5E%7B7x%7D%7D%7B7%7D%20%2B%20%5Cfrac%7Be%5E%7B7x%7D%7D%7B7%2A7%7D%20%5C%5C%5Cint%5Climits%20%7Bxe%5E%7B7x%7D%7D%20%5C%2C%20dx%20%3D%20%5Cfrac%7Bxe%5E%7B7x%7D%7D%7B7%7D%20%2B%20%5Cfrac%7Be%5E%7B7x%7D%7D%7B49%7D)